Impact of religious experiences on Islamic stock market return. (13th September 2019) - Jawada, Marwa; Ellouz, Siwar
This paper aims to examine the Islamic stock market behaviour in different periods of the Islamic calendar. It focuses on how the mechanisms underlying a religious occasion can influence the stock market return. This research uses daily price index data for a wide range of Islamic stock index market around the world with an event study methodology, to detect the existence of Islamic calendar anomalies. For a total of 724 events examined, the results confirm that religiosity influences investor behaviour, by reporting stock return anomalies on the pre- and post-holidays periods. The rationalisations proposed for the existence of these anomalies were essentially of a behavioural nature. The collective experience of Islamic occasions can affect the mood of its observers, strengthen their sense of belonging and promote solidarity in the Muslim world, leading to optimistic beliefs that extend to investment decisions. Sentiment related to religious event is generally used to explain the results found in the research.